Psychophysiological and Dual-Task Effects of Biofeedback and Neurofeedback Interventions in Airforce Pilots: A Pilot Study - Juan Pedro Fuentes-García; Juan Luis Leon-Llamas; Santos Villafaina (Sensors)
(1) Background: Neurofeedback (NFB) and biofeedback (BFB) have been shown to reduce stress, enhance physiological self-regulation, improve cognitive performance, and accelerate response times. Stimulating the sensorimotor rhythm (12–15 Hz) is particularly effective in improving working memory and selective attention. However, most studies on air force pilots focus on addressing post-traumatic stress disorder rather than investigating how these interventions might enhance performance and safety during flights, as explored in the present study. (2) Methods: Twelve Spanish Air Force fighter pilot trainees (mean age = 22.83 (0.94) years) participated in the study. Six pilots underwent 24 sessions of combined NFB and BFB training (experimental group), while six served as controls. (3) Results: The experimental group demonstrated improved heart rate variability during baseline, alarm sounds, math tasks, and real flights, which is indicative of greater parasympathetic modulation. A significant decrease in the Theta/SMR ratio was observed in the experimental group during the same conditions, suggesting improved focus, with lower values than the control group. Cognitive performance improved in the experimental group, with higher accuracy and a greater number of completed operations during math tasks. Regarding dual-task performance, the experimental group showed lower reaction time and a better ratio taps/reaction post-intervention. Psychological benefits included reduced cognitive, somatic, and state anxiety levels, along with increased self-confidence. (4) Conclusions: Neurofeedback and biofeedback training, integrated with real flights, simulators, and virtual reality, can enhance physiological regulation, cognitive performance, and emotional resilience, contributing to improved performance and safety in air force pilots.